2017
DOI: 10.1097/eja.0000000000000500
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress, burnout and personality traits in Dutch anaesthesiologists

Abstract: fentanyl patch for several weeks prior to her death. 2 In this sense at least, the patient was not opioid nontolerant. Second, although we agree that the individual variation of tolerance is substantial, we were also quite surprised that a nonopioid-naïve patient could commit suicide with her standard patch. This may be an effect of the quicker rate of increase in blood concentration by oral ingestion, rather than the absolute concentration. And third, given that chronic pain itself is an independent risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Sleep is a vital physiological process, but shift work may increase the risk of cognitive impairment among night-shift medical staff over time [ 20 ]. Many night shift nurses and physicians show signs of mood disorders, burnout syndrome, and memory and attention problems [ 2 , 21 , 22 ]. As shift work is common and necessary in many professions, passive effects caused by overload work and disturbed biorhythm are substantial and should be addressed to prevent serious long-term complications.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep is a vital physiological process, but shift work may increase the risk of cognitive impairment among night-shift medical staff over time [ 20 ]. Many night shift nurses and physicians show signs of mood disorders, burnout syndrome, and memory and attention problems [ 2 , 21 , 22 ]. As shift work is common and necessary in many professions, passive effects caused by overload work and disturbed biorhythm are substantial and should be addressed to prevent serious long-term complications.…”
Section: Discussionmentioning
confidence: 99%
“…This study will be the rst to evaluate the potential effectiveness of VR technology in reducing stress among night-shift anesthesiologists. Work overload, long working hours, and continuous noise pollution [31,32] are among the factors that cause physical and mental problems among anesthesiologists, such as psychological distress, burnout syndrome (BOS), and memory and attention problems [33,34]. It has been reported that mental fatigue is the main cause of medical error among anesthesiologists [35] as well as the main reason for the high proportion of suicides among these doctors [36].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the problem of occupational stress and burnout in anesthesiologists has gained attention and awareness in different countries. [10,11] Burnout prevalence among anesthesiologists varied greatly from country to country. [7] To our knowledge, there has been no previous research till now on the burnout level of anesthesiologists from high altitude areas, where the ecological condition and sociodemographic factors are different.…”
Section: Discussionmentioning
confidence: 99%